Hamilton Naki: From Gardening to Greatness: On The Shoulder of Giants - Hennessy, Conor; Ngetich, Elisha; Brameier, Devon (Journal of the Nuffield Department of Surgical Sciences, 2020)
In the wake of the first heart transplant 53 years ago in Cape Town, Professor Christian Barnard found himself to be the subject of much media attention with his face appearing on the cover of Time magazine, highlighting the significance of this milestone in transplant surgery. While the importance of this moment in the history of transplant surgery has never been in dispute, the roster of people who made this achievement possible has, with the presence of one particular individual being the source of great controversy in the 53 years following the procedure.